Analysis of applying the health-saving technologies in physical education process of student - Ella E-O. Mendot, Uliana A. Magbyn, Elena M. Ag-ool, Eduard K-O. Kyrgys, Rada D. Saaya, Emma E-O. Mendot, (Opción, 2019)
The article is devoted to defining of priority tasks of the physical education of the Tuvan State University‟s students. The method of analysis of the theoretical research on the methods of teaching physical education at a university was applied. As a result, the essence of health-saving technologies in education ensures intellectual and physical efficiency and stimulates activity, interests, and needs for knowledge. As a conclusion, it is necessary to find out and introduce the new effective forms of sports leisure that is popular among young people such as orienteering, water and mountain tourism, mountaineering, parachuting and hang gliding.